Investor Understanding and Risk Mispricing in Initial Public Offering Markets: A Behavioural Perspective on Investor Risk Perception - Puri, Tina; Kachitsa, Charles Leyman; Obohwemu, Kennedy Oberhiri; Abiodun, Olumuyiwa; Fard, Jalaleddin Kazemi; Jannat, Sayma Akter (International Interdisciplinary Business Economics Advancement Journal, 2026)
Initial public offerings represent an important mechanism through which firms raise capital from public markets while providing investors with opportunities to participate in early stages of corporate growth. Despite extensive disclosure requirements designed to reduce information asymmetry, IPO markets continue to exhibit persistent patterns of mispricing and speculative investment behaviour. This paper examines how investors interpret and respond to risk disclosures contained in IPO prospectuses. Drawing on established research in corporate finance and behavioural finance, the analysis shifts attention from firm-level financial metrics toward investor cognition and behavioural response. The paper argues that investor awareness of risk does not necessarily translate into accurate risk assessment or rational pricing behaviour. Behavioural influences such as optimism, overconfidence, and herd behaviour shape how investors interpret prospectus information and evaluate investment opportunities. A conceptual framework is developed that explains how prospectus disclosures interact with investor cognition and market sentiment to produce risk mispricing. The paper contributes to research on IPO markets through a behavioural interpretation of investor awareness and highlights implications for disclosure design, investor education, and regulatory policy.